2005
DOI: 10.1099/mic.0.27883-0
|View full text |Cite
|
Sign up to set email alerts
|

Acclimation of unicellular cyanobacteria to macronutrient deficiency: emergence of a complex network of cellular responses

Abstract: Cyanobacteria are equipped with numerous mechanisms that allow them to survive under conditions of nutrient starvation, some of which are unique to these organisms. This review surveys the molecular mechanisms underlying acclimation responses to nitrogen and phosphorus deprivation, with an emphasis on non-diazotrophic freshwater cyanobacteria. As documented for other micro-organisms, nutrient limitation of cyanobacteria elicits both general and specific responses. The general responses occur under any starvati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
190
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 219 publications
(199 citation statements)
references
References 91 publications
(93 reference statements)
8
190
0
1
Order By: Relevance
“…Limnothrix and Pseudoanabaena (Pseudoanabaenaceae) were strongly attached to all the glassware and grew slowly though with biofilms and green plates on the liquid surface, with high EPS/CHO ratios in the exponential growth phase. The sudden increase of CHO after 1 month of growth, missing in the EPS production, suggests an increase in storage polysaccharides, also clearly visible as granules in the microscope, a cellular response probably related to a nutrient depletion (Schwarz and Forchhammer 2005).…”
Section: Discussionmentioning
confidence: 95%
“…Limnothrix and Pseudoanabaena (Pseudoanabaenaceae) were strongly attached to all the glassware and grew slowly though with biofilms and green plates on the liquid surface, with high EPS/CHO ratios in the exponential growth phase. The sudden increase of CHO after 1 month of growth, missing in the EPS production, suggests an increase in storage polysaccharides, also clearly visible as granules in the microscope, a cellular response probably related to a nutrient depletion (Schwarz and Forchhammer 2005).…”
Section: Discussionmentioning
confidence: 95%
“…In our model, chlorophyll synthesis is not influenced by the P status of the cell but in contrast it is proportional to the N content of the phytoplankton cells. This was motivated by the fact that under Nlimited conditions authors have shown a bleaching of phytoplankton cells as a result of decreasing chlorophyll content (Schwarz and Forchhammer, 2005). High N:P environment combined with P-limitation of phytoplankton growth increase the uncoupling between GPP and growth and thus increase P.E.R.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, sulfate concentration in average seawater is much higher (~185mg/L) (Nelson, 2007). Deficiency of sulfur or other major essential nutrients can result in degradation of the cyanobacterial light-harvesting complex, the phycobilisome (known as photobleaching), as well as modification of other metabolic pathways and physiological processes (Collier et al, 1994;Schwarz and Forchhammer, 2005). Thus, the incurable plasmid pANL is likely to provide important advantages for the fresh water cyanobacterium S. elongatus PCC 7942 because it encodes almost all of the components required for adaptation to sulfur deficiency.…”
Section: Discussionmentioning
confidence: 99%